Programa PNAD: uma construção científica - Nogueira, Elizabeth Saramela (1993)
Study about the review process of the conceptual and methodological parameters that guide the National Research per Domicile Sampling (PNAD) of the Instituto Brasileiro de Geografia e Estatistica (IBGE) Organization in the period between 1989 and 1992. Its purpose is to show the statistical production process, as well as to understand the relationships that exist among object, theory and method in measurement- oriented surveys. In the ligth of reflections about the building of s cientific knowledge and the role of method in the survey process, the specificity of the statistical method is discussed. The results indicate that PNAD's construction process is affirmed as a scientific act.